Prosocial Attitudes and Behavior of Students: The Effects of Service Learning - V. S. Nikolskiy; P. A. Ambarova; N. V. Shabrova (Высшее образование в России, 2025)
Modern higher education is increasingly focused on training not only qualified specialists, but also socially responsible citizens who are able to actively participate in solving social problems. In this regard, there is an increasing interest in approaches that stimulate the development of prosocial attitudes and behavior among students. One of these promising areas is service learning», which combines academic learning with real-world activities aimed at benefiting society. In Russian practice, this approach is undergoing a stage of active development, which necessitates its comprehensive study and adaptation to domestic social and educational realities.The relevance of the research is due to the increasing demand from society for university graduates with not only professional knowledge, but also developed prosocial qualities such as empathy, leadership, and the ability to communicate effectively. In the context of global challenges and social problems, the formation of an active civic position and readiness for constructive interaction among young people is becoming especially important.The academic novelty of the research lies in the empirical substantiation of the influence of the “Service Learning” approach on the formation of prosocial attitudes and behavior of students in Russian universities. For the first time, a large-scale (n=1745) study was conducted, which makes it possible to evaluate not only students’ ideas about the social significance of their future profession, but also the development of personal qualities in demand in prosocial activities. The specific mechanisms and factors contributing to the formation of prosocial attitudes and behavior of students in the framework of the implementation of Service-Learning projects have been identified.The article contributes to the development of academic discussion on the formation of prosocial attitudes and behavior in higher education by offering empirical evidence substantiating the effectiveness of the “Service-Learning” approach and its impact on the development of relevant qualities in students. The results of the study make it possible to expand the theoretical understanding of this approach and develop practical recommendations for its effective implementation in Russian universities. The article also stimulates further research in the field of prosocial behavior and the search for effective methods of its formation in the higher education system.